Identification of Oleanolic Acid as Allosteric Agonist of Integrin αM by Combination of In Silico Modeling and In Vitro Analysis - Jin, Lu; Han, Xiaoyu; Zhang, Xinlei; Zhao, Zhimin; Ulrich, Judith; Syrovets, Tatiana; Simmet, Thomas (Frontiers in Pharmacology, 2021)
Oleanolic acid is a widely distributed natural product, which possesses promising antitumor, antiviral, antihyperlipidemic, and anti-inflammatory activities. A heterodimeric complex formed by integrin αM (CD11b) and integrin β2 (CD18) is highly expressed on monocytes and macrophages. In the current study, we demonstrate that the I domain of αM (αM-I domain) might present a potential cellular target for oleanolic acid. In vitro data show that oleanolic acid induces clustering of αM on macrophages and reduces their non-directional migration. In accordance with experimental data, molecular docking revealed that oleanolic acid binds to the αM-I domain in its extended-open form, the dominant conformation found in αM clusters. Molecular dynamics simulation revealed that oleanolic acid can increase the flexibility of the α7 helix and promote its movement away from the N-terminus, indicating that oleanolic acid may facilitate the conversion of the αM-I domain from the extended-closed to the extended-open conformation. As demonstrated by metadynamics simulation, oleanolic acid can destabilize the local minimum of the αM-I domain in the open conformation partially through disturbing the interactions between α1 and α7 helices. In summary, we demonstrate that oleanolic acid might function as an allosteric agonist inducing clustering of αM on macrophages by shifting the balance from the closed to the extended-open conformation. The molecular target identified in this study might hold potential for a purposeful use of oleanolic acid to modulate chronic inflammatory responses.